Digital Ethics Based on Islamic Education and Thought: An Approach to Technological Innovation in the Development of Digital Society - Fahriah Fahriah; Ani Cahyadi; Hamrani Hamrani (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to develop a framework of digital ethics based on Islamic education and thought as a conceptual approach to addressing the increasingly complex challenges of digital society development. The main focus of this research is to integrate Islamic ethical values with the dynamics of digital technological innovation in order to foster responsible, ethical, and sustainable digital behavior. The study employs a qualitative method using a library research approach. Data were analyzed through content analysis of primary sources, namely the Qur’an and Hadith, as well as secondary sources consisting of recent scholarly literature in digital ethics, Islamic education, and the sociology of technology. The findings indicate that Islamic ethical principles such as trustworthiness (amanah), proper conduct (adab), honesty, and responsibility can serve as a normative foundation for building digital ethics in the digital era. The integration of these values provides moral guidance in the use of technology, particularly in addressing issues such as misinformation, cyberbullying, data privacy, and unethical digital behavior. The novelty of this study lies in the development of a conceptual model of digital ethics that integrates the epistemology of Islamic education with modern technological innovation principles. This model is not only normative-theological but also practical and applicable in the context of digital society development, offering a new approach to digital ethics studies grounded in Islamic values while remaining responsive to contemporary technological advancements